Pengaruh Promotion, Service Quality, and Customer Experience Terhadap Loyalitas Nasabah Pada Bank Syariah Indonesia Cabang Medan Pulo Brayan - Fadilla, Fadilla (Jurnal Ilmiah Ekonomi Islam, 2024)
This study was conducted with the aim of analyzing the influence of promotions, service quality and customer experience on customer loyalty at BSI Medan Pulo Brayan Branch. The chosen method is “field research”, which involves the use of a quantitative approach to the analysis. The results of the analysis show that the three variables have a positive and significant influence on customer loyalty. Promotions, service quality and customer experience are important factors in building customer loyalty. Banking institutions need to improve the quality of electronic-based services to increase customer satisfaction. Future research can compare Islamic and conventional banks, and involve samples from certain groups such as students. To better retain and attract customers, this research is important to help banks develop better marketing strategies and improve service quality.